PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 2011 TENTANG PERUMAHAN DAN KAWASAN PERMUKIMAN TERHADAP PERLINDUNGAN HAK KONSUMEN DALAM JUAL BELI PERUMAHAN - Megawati, Ni Ketut Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 5 No 1 (2016), 2016)
A mismatch between the administrative documents or the physical characteristics of a property offered in a contract and the actual conditions received by the client becomes an important problem in a property business. The property, which is the object of an agreement, should be in line with the legal aspects required by the legislation. The purpose of this study is to understand the legal condition of registering a property as the object of an agreement, by using consumer protection law in relation to property sales (i.e., Legislative Decree number 1 of 2011) as the perspectives. This study used normative legal framework based on Law and concept approaches as its research method. Several primary laws were collected and analyzed by a qualitative descriptive method. This study found that a property could be included as the object of an agreement if it fulfills the terms and conditions written in the Article 42 Clause 1 of Legislative Decree number 1 of 2011 on Real Estate and Residential Areas. Furthermore, a property can be an object of sales agreement if they meet several criteria written in the State Minister of Community Estate Decree’s number 09/KPTS/M/1995, with the date of issuance on 23 June 1995, about the sale and purchase of a property. It can be argued that the Legislative Decree number 1 of 2011 on Real Estate and Residential Areas might not offer a comprehensive protection to the consumer rights, and subsequently inflict physical and mental harm to the consumers.
Keywords: Agreement; consumer rights; property; real estate